TEACHER TRAINING AND PROFESSIONAL DEVELOPMENT IN ISLAMIC EDUCATION - Sugito Sugito (Education Studies and Teaching Journal (EDUTECH), 2024)
This research explores the importance of integrating Islamic values ​​in teacher training and its impact on professional identity and teaching effectiveness. The aim of this research is to analyze existing studies regarding the integration of Islamic values ​​in teacher training curricula and evaluate their impact. Using a systematic literature review approach, this research found that Islamic values ​​applied in teacher training contributed positively to the development of professional identity and increased teaching effectiveness. The implications of this research indicate that the teacher training curriculum needs to be revised to include Islamic values, in order to produce educators who are more ethical and responsive in the context of Islamic education.